2017
DOI: 10.21767/1791-809x.1000505
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Back Pain and Associated Factors among Bank Staff in Selected Banks in Kigali, Rwanda: A Cross Sectional Study

Abstract: Background: Banking has made people run and develop their businesses well, use of computers is a revolution in which work is made easier in banks, it has however been revealed to cause musculoskeletal pain. Computer use requires prolonged sitting or improper body alignment which strains the vertebral column causing back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
6
13
0
1
Order By: Relevance
“…Respondents sitting with their back twisted were 3.6 times more likely to develop WMSDs than sitting with their back straight. This finding was consistent with studies done in Rwanda [13] and Dutch [26]. On the other hand, respondents sitting with their back bent were 4 times more likely to develop WMSDs than sitting with a straight aligned back.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Respondents sitting with their back twisted were 3.6 times more likely to develop WMSDs than sitting with their back straight. This finding was consistent with studies done in Rwanda [13] and Dutch [26]. On the other hand, respondents sitting with their back bent were 4 times more likely to develop WMSDs than sitting with a straight aligned back.…”
Section: Discussionsupporting
confidence: 91%
“…The sample size for the magnitude of WMSDs was computed based on single proportion formula by using proportion of WMSDs from a previous study conducted in Rwanda among bank workers who accounted for 45.8% [13] and a 95% confidence interval (CI) and margin of error of 5% and 10% non-response rate. Since the sampling method was multi-stage, this study used design effect of 2 making a total sample size of 838.…”
Section: Sample Size and Sampling Proceduresmentioning
confidence: 99%
“…The one-month prevalence of LBP among bank employees is 36.6%. Similar to our research, a cross-sectional study conducted in Kigali, Rwanda, found that 45.8% of bank staffs reported LBP during the one year [25]. Another study conducted in Nigeria found 12 months prevalence rate of office workers was 38.0% [26].…”
Section: Discussionsupporting
confidence: 88%
“…This study fi nding is similar to study conducted in Kigali, Rwanda, in which, respondents having no break off during working time were 3.9 times more likely to have low back pain compared to those who had time to rest during the workday. 31 This may be due to lack of time to rest which exaggerates the risk of getting low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…This fi nding is similar to fi ndings from studies conducted in Kigali, Rwanda and Iran which shows respondents who frequently use a computer were 3.5 and 3.2 times more likely to have low back pain as compared to those who didn't use a computer during their working time respectively. 21,31 The possible explanation for this fi nding might be due to the presence of a computer in the workplace leads to a set of peculiar characteristics of the workstation which require the workers to stay in a static posture for long periods.…”
Section: Discussionmentioning
confidence: 99%